1996
DOI: 10.1590/s0103-84781996000100021
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre as provas de ELISA e imunofluorescência indireta (IFI) para detectar anticorpos contra Babesia bovis

Abstract: Comparou-se o desempenho de um kit de ELISA para detectar anticorpos contra Babesia bovis, em hemoparasita bovino, com o teste de Imunofluorescência Indireta (IFI) usualmente empregado em rotina sorológica. Sobre 97 amostras de soros oriundas de uma região livre de carrapatos e hematozoários, o teste de ELISA demonstrou uma especificidade de 98.9% contra 97.9% do teste de IFI. Ambos os testes apresentaram uma sensibilidade de 100% quando utilizados sobre 22 amostras de soro de bovinos experimentalmente infecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The clinical signs of the disease are fever, anemia, anorexia, lethargy, ataxia, tachypnea, hemoglobinuria, and muscle tremors (GUGLIELMONE, 1995;SOARES et al, 2000;SILVA et al, 2007;SINGH et al, 2009). The economic importance of this disease is due to the high animal morbidity and mortality especially among calves, and to its effects on weight gain and milk production, leading to the use of costly disease control and prevention measures (MARTINS et al, 1996;GRISI et al, 2002;BARROS et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical signs of the disease are fever, anemia, anorexia, lethargy, ataxia, tachypnea, hemoglobinuria, and muscle tremors (GUGLIELMONE, 1995;SOARES et al, 2000;SILVA et al, 2007;SINGH et al, 2009). The economic importance of this disease is due to the high animal morbidity and mortality especially among calves, and to its effects on weight gain and milk production, leading to the use of costly disease control and prevention measures (MARTINS et al, 1996;GRISI et al, 2002;BARROS et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…; the most used are the indirect immunofluorescence assay (IIFA) and the indirect immunoenzimatic ELISA assay (IIEA), as they are sensitive and specific tests and therefore considered appropriate for epidemiological studies of this disease (SANTOS et al, 2001;OSAKI et al, 2002;JULIANO et al, 2007). But a comparative study between IIFA and ELISA demonstrated that the latter was more sensitive and specific, allowing the analysis of a larger number of samples (MARTINS et al, 1996;ARAÚJO et al, 1998).…”
Section: Introductionmentioning
confidence: 99%